THE PRICE MECHANISM FUNCTION OF CURLY RED CHILLY IN THE CENTER OF PRODUCTION AND WHOLESALER - Sukmawati, Dety; Ning Srimenganti (Dinasti International Journal of Digital Business Management, 2020)
The problem of red chili related to price fluctuations has always been a concern for farmers.Therefore, an increase in the production of agricultural commodities including chili horticultural commodities needs to be accompanied by improvements to the marketing system. These research was quantitative research, data collection was done by means of a survey of time series . The data used are time series data and supporting data which come from: Information center of price at production center, and price information at West Java Food Crop Agriculture Agency. From the amount of data (included observation) which amounted to 72 data. The technic analyzed used multivariate. ,the rational expectation hypothesis of the supply function was analyzed by the EVIEWS 8. the results of price analysis in Cikajang have a dominant influence on prices in the PIKJ and vice versa, the results of the analysis show that an increase in price of 1 rupiah in Cikajang will increase the price in PIKJ 0.7679 rupiah, or an increase in price of 76.79% meaning an increase in prices in production centers will raised the price of 76.79% in the PIKJ. PIKJ will quickly respond to price increases in production centers even though the distance from production centers to PIKJ was very far, the flow of price information that occurs was actually one-way from PIKJ to production centers. The response to the high price increase was seen that the PIKJ was a price determinant and when viewed from the marketing actors involved in it turns out there were farmers in the production center which were dealers or traders in the PIKJ.